2009
DOI: 10.1097/aog.0b013e3181af6931
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Neonatal Outcome in Low-Risk, Spontaneous, Singleton, Late Preterm Deliveries

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
104
7
12

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(139 citation statements)
references
References 28 publications
16
104
7
12
Order By: Relevance
“…The rates of neonatal complications observed in twins born at 34, 35, and 36 weeks of gestation did not differ significantly (except for antibiotic therapy between 34 and 35 weeks). Melamed et al (2009) studied neonatal complications in singletons and revealed a continuous relationship between gestational age and newborns' morbidity between 32 and 36 weeks of gestation, without any threshold of gestational age. The neonatal morbidity rate decreased only after completed 37 weeks of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…The rates of neonatal complications observed in twins born at 34, 35, and 36 weeks of gestation did not differ significantly (except for antibiotic therapy between 34 and 35 weeks). Melamed et al (2009) studied neonatal complications in singletons and revealed a continuous relationship between gestational age and newborns' morbidity between 32 and 36 weeks of gestation, without any threshold of gestational age. The neonatal morbidity rate decreased only after completed 37 weeks of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…Morbidity and mortality in newborn babies is directly related to gestational age at delivery, 13,14 which is an important clinical message because the decision to deliver the fetus preterm is often taken without medical indication. By contrast with other studies, our fi ndings show that infants exposed to chemotherapy in utero had a lower birthweight at the same gestational age than did infants not exposed to chemotherapy, a fi nding that was not aff ected by the amount of chemotherapy given and one that we believe is clinically irrelevant (because such low birthweight would not aff ect an otherwise healthy baby).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, they are physiologically and metabolically immature (2,8,10). Consequently, they are at a higher risk for morbidity when compared with full-term infants (4,7,10,11), such as respiratory distress (8,(12)(13)(14), hyperbilirubinaemia (8,(15)(16)(17), temperature instability (8,18), feeding difficulties (8,19,20), hypoglycaemia (8,18) and need for NICU admission (7,8,21).…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent years, some concern rose in the literature because of the longer hospital stay and the higher costs of the latter group. Simultaneously, an increase in the rate of late preterm deliveries was observed over the last two decades (3), another reason why attention focused on their short-term and long-term outcome (1,(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%